Determination of the Minimum Wave Speed for the Modelling of Ventilated Cavitation - 陈婷 张宇宁 杜小泽 (Chinese physics letters, 2016)
Ventilated cavitation plays an important role on the drag reduction of underwater vehicles and surface ships. For the modelling of ventilated cavitation, the minimum speed of the pressure wave is a crucial parameter for the closure of the pressure-density coupling relationship. In this study, the minimum wave speed is determined based on a theoretical model coupling the wave equation and the bubble interface motion equation. The influences of several paramount parameters （e.g., frequency, bubble radius and void fraction） on the minimum wave speed are quantitatively demonstrated and discussed. Compared with the minimum wave speed in the traditional cavitation, values for the ventilated cavitation are much higher. The physical mechanisms for the above difference are briefly discussed with the suggestions on the usage of the present findings.